How Local Media Coverage of Voter Fraud Influences Partisan Perceptions in the United States. (June 2018) - Udani, Adriano; Kimball, David C.; Fogarty, Brian
Abstract: Extant findings show that voter fraud is extremely rare and difficult to prove in the United States. Voter's knowledge about voter fraud allegations likely comes through the media, who tend to sensationalize the issue. In this study, we argue that the more voters are exposed to media coverage of voter fraud allegations, the more likely that they will perceive that voter fraud is a frequent problem. We merge the 2012 Survey of Performance of American Elections with state-level media coverage of voter fraud leading up to the 2012 election. Our results show that media coverage of voter fraud is associated with public beliefs about voter fraud. In states where fraud was more frequently featured in local media outlets, public concerns about voter fraud were heightened. In particular, we find that press attention to voter fraud has a larger influence on Republicans than Democrats and Independents. We further find that media coverage of voter fraud does not further polarize partisan perceptions of voter fraud. Rather, political interest moderates state media coverage on voter fraud beliefs only among Republicans. Last, our results provide no support that demographic changes, approval of election administration, or information concerning actual reported voting irregularities have any discernable effects on partisan perceptions.